Special Group on Targeting Ten Million Employment Opportunities Per Year Employment Generating Growth - Planning Commission (Planning Commission, 2002)
The Special Group on targeting ten million employment opportunities per year over the Tenth Plan period has been constituted by the Planning Commission to explore appropriate policies and programmes for generating targeted gainful employment for 50 million persons over the Tenth Plan. The composition and details of the Terms of Reference are given in Annexure “C”. The Special Group accordingly examined all the relevant studies and sources of information for assessing the present status of employment and unemployment in India and by interacting with relevant Ministries and agencies, has attempted to recommend appropriate macro and sectoral policies and “programmes in specific areas” needed to generate the aforesaid employment opportunities over the Tenth Plan.
Government of India Planning Commission
Government of India Planning Commission